2015
DOI: 10.1111/aae.12051
|View full text |Cite
|
Sign up to set email alerts
|

Buried far from home: Sasanian graves at Jebel al‐Emeilah (Sharjah, UAE)

Abstract: Human skeletons were recovered in two unmarked burials blown to the surface of a dune south‐west of Jebel al‐Emeilah in the Central Region of the Sharjah Emirate (UAE). Sasanian stamp seals were found associated with one of the individuals. A bone fragment of this individual provided a direct radiocarbon date placing it in the Middle Sasanian period. With the aid of strontium isotope analysis it was possible to determine that the two individuals were immigrants to the area that is now part of the UAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…30; Potts 1997; Benton & Potts 2010; Jasim 2012: 263; Düring & Olijdam 2015: 102–103; Kutterer et al . 2015). Other unpublished examples have recently been revealed 15km inland from the coast at Liwa, north of Sohar, and the Wadi al-Arad, where as many as 50 tombs are located (S. Laurenza pers.…”
Section: Discussionmentioning
confidence: 99%
“…30; Potts 1997; Benton & Potts 2010; Jasim 2012: 263; Düring & Olijdam 2015: 102–103; Kutterer et al . 2015). Other unpublished examples have recently been revealed 15km inland from the coast at Liwa, north of Sohar, and the Wadi al-Arad, where as many as 50 tombs are located (S. Laurenza pers.…”
Section: Discussionmentioning
confidence: 99%
“…In later sources we read anecdotes about traders from around the Gulf coming to Oman: a good example is the ancestor of the famous early Islamic Muhallabid family Abū Ṣufra, who in polemical accounts is said to have been a Persian Zoroastrian weaver from Kharg originally called Baskhara b. Bahbūdhān, who migrated to Oman (Ibn Rusta, : 205–206; Hinds, : 12–13, n. 10; Morony, –2002: 33–34). Radiocarbon and strontium isotope analysis from two burials in Sharjah in the United Arab Emirates has now confirmed that during the Sasanian period some migrants did come to south‐east Arabia from other parts of the Sasanian empire, although in what capacity we can only guess (Kutterer, Jasim, & Yousif, ). Otherwise, although certainly not implausible, the trade argument seems to be based on thinly evidenced claims for the prosperity of Gulf merchant activity in late antiquity, together with a historiographical trend that sees empires as the geo‐political manifestations of economic systems .…”
Section: Oman and ēRānšahrmentioning
confidence: 98%
“…This information is based on a geological map of the Northern Emirates produced by the British Geological Survey (Ministry of Energy, Petroleum and Minerals, ). A detail of this map for the area under discussion is found in A. Kutterer, Jasim and Yousif (). The plain east of BHS18 has a slight inclination from east to west, which causes water from the mountains to flow across the plain, both on the surface and underground.…”
Section: Geological Setting Of Al‐buhais 18mentioning
confidence: 99%
“…For the respective area, A. Kutterer et al. (: 47–50) have already discussed the related problems. As a pragmatic solution, it was decided to use the wood of trees as a source for securely localised 87/86 Sr ratios.…”
Section: Geological Setting Of Al‐buhais 18mentioning
confidence: 99%
See 1 more Smart Citation